Targeting prostate cancer: Prostate-specific membrane antigen based diagnosis and therapy - Wüstemann, Till; Haberkorn, Uwe; Mier, Walter (Medicinal research reviews, 2019)
The high incidence rates of prostate cancer (PCa) raise demand for improved therapeutic strategies. Prostate tumors specifically express the prostate-specific membrane antigen (PSMA), a membrane-bound protease. As PSMA is highly overexpressed on malignant prostate tumor cells and as its expression rate correlates with the aggressiveness of the disease, this tumor-associated biomarker provides the possibility to develop new strategies for diagnostics and therapy of PCa. Major advances have been made in PSMA targeting, ranging from immunotherapeutic approaches to therapeutic small molecules. This review elaborates the diversity of PSMA targeting agents while focusing on the radioactively labeled tracers for diagnosis and endoradiotherapy. A variety of radionuclides have been shown to either enable precise diagnosis or efficiently treat the tumor with minimal effects to nontargeted organs. Most small molecules with affinity for PSMA are based on either a phosphonate or a urea-based binding motif. Based on these pharmacophores, major effort has been made to identify modifications to achieve ideal pharmacokinetics while retaining the specific targeting of the PSMA binding pocket. Several tracers have now shown excellent clinical usability in particular for molecular imaging and therapy as proven by the efficiency of theranostic approaches in current studies. The archetypal expression profile of PSMA may be exploited for the treatment with alpha emitters to break radioresistance and thus to bring the power of systemic therapy to higher levels.
First published: 17 May 2018
Gesehen am 09.04.2020